THE EFFECT OF TEACHING ENGLISH THROUGH OPEN-ENDED QUESTIONS STRATEGY IN IMPROVING STUDENTS’ SPEAKING SKILL (An Experimental Research at 9th Grades Students in SMP ADVENT LUBUK BAJA BATAM Academic Year 2022/2023) - Sinaga, Juwita Boneka (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2023)
AbstractThe problem discussed in this thesis is how the effect of the English learning method using an open-ended questions strategy to improve speaking skills in ninth grade students at the ADVENT Junior High School Lubuk Baja Batam. The purpose of this study was to determine whether there was an effect of the English learning method using an open-ended questions strategy in improving students’ speaking skill. The theories in this research are related to speaking skill and open-ended questions strategy.This research used quantitative research. Furthermore, this research used a pair of instruments to assess and collect data from both variables. To assess students’ critical thinking skill, researcher used a holistic scoring rubric critical thinking skills designed by Facione and Gittens, and to assess the speaking skill, the researcher used an Oral Proficieny scoring categories designed by Brown in his book Language Assessment - Principles and Classroom Practices. The researcher used the Independent Sample T-test formula to measure the two variables, with the calculation obtained the result of t=6.570 and matched it with significance level 0.05;n=40 which is 2.024. So, it can be concluded that there is a significant effect of the open-ended questions strategy in improving students’ speaking skill. According to the results of data accumulation, it can be concluded that the method of learning English using an open-ended questions strategy has a significant effect in improving students’ speaking skill.